Gabriel J. Zanotti, Economía de mercado y doctrina social de la iglesia, Ed. de Belgrano, Colección Textos, Buenos Aires, 1985, 120 pp. - Mallea, Ana M. (1986)
Fil: Mallea, Ana M. Investigador independiente